INFORMATION SUPPORT FOR THE TRANSPORT AND LOGISTICS COMPANY - T. Bogdanova; K. Kuznetsov (Вестник университета)
The article describes the issues of information support activities of transport and logistics companies in connection with the peculiarities of their functioning. The analysis of the major databases characterizing the state of the external and internal environments of transport and logistics companies, which allowed to formulate the problems and trends of development of information security. Examples of public information databases and their impact on the performance of the transport and logistics companies. The study will serve as a basis for the development of recommendations to improve the quality of information support of the activities of transport and logistics companies.